2021
DOI: 10.9734/ajrid/2021/v6i230192
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge, Attitude, Perception and Practices on Rabies Disease in the GA East Municipality, Ghana

Abstract: Background: Rabies is one of the neglected tropical zoonotic diseases caused by a virus. It belongs to the Rhabdoviridae [1]. It is a disease that is commonly found in animals but can easily effect human [2]. Where there are animal reservoirs, rabies is commonly spread. The general objective of this study to evaluate differences in knowledge, attitude and perception about rabies, among the residence in Ga East. Methods: A cross-sectional study was used in this study using purposive sampling technique. Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Several studies have reported on rabies in Ghana. These include epidemiology and control measures (Addy, 1985; Alonge & Abu, 1984; Belcher et al., 1976; Lopes et al., 2018); surveillance systems (Afakye et al., 2016; Guri et al., 2020); human rabies outbreaks (Amoako et al., 2021; Apanga et al., 2016; Dsane‐Aidoo et al., 2022; Laryea et al., 2017; Punguyire et al., 2017); dog bites and rabies (Abuh et al., 2017; Addai & Nuertey, 2018; Adomako et al., 2018; Dsane‐Aidoo et al., 2022; Eliezer, 2016; Kenu et al., 2018; Korash & Ameme, 2017; Punguyire et al., 2017, 2020); dog population structure (Tasiame et al., 2019); dog‐associated pig rabies (Tasiame et al., 2016); rabies virus in dogs slaughtered for meat consumption (Tasiame et al., 2021); knowledge, attitudes, perceptions, practices and beliefs (Awuni et al., 2019; Tettey, 1998; Turkson & Wi‐Afedzi, 2020; Vetsi et al., 2021) and lineage of rabies virus in Ghana (Hayman et al., 2011). However, no studies have reported on the space–time pattern of the disease countrywide on a national level.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported on rabies in Ghana. These include epidemiology and control measures (Addy, 1985; Alonge & Abu, 1984; Belcher et al., 1976; Lopes et al., 2018); surveillance systems (Afakye et al., 2016; Guri et al., 2020); human rabies outbreaks (Amoako et al., 2021; Apanga et al., 2016; Dsane‐Aidoo et al., 2022; Laryea et al., 2017; Punguyire et al., 2017); dog bites and rabies (Abuh et al., 2017; Addai & Nuertey, 2018; Adomako et al., 2018; Dsane‐Aidoo et al., 2022; Eliezer, 2016; Kenu et al., 2018; Korash & Ameme, 2017; Punguyire et al., 2017, 2020); dog population structure (Tasiame et al., 2019); dog‐associated pig rabies (Tasiame et al., 2016); rabies virus in dogs slaughtered for meat consumption (Tasiame et al., 2021); knowledge, attitudes, perceptions, practices and beliefs (Awuni et al., 2019; Tettey, 1998; Turkson & Wi‐Afedzi, 2020; Vetsi et al., 2021) and lineage of rabies virus in Ghana (Hayman et al., 2011). However, no studies have reported on the space–time pattern of the disease countrywide on a national level.…”
Section: Introductionmentioning
confidence: 99%